Implementasi dan Analisa Keamanan Jaringan IDS (Intrusion Detection System) Menggunakan Suricata Pada Web Server - Elsa Stephani; Fitri Nova; Ervan Asri (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2020)
The defense system against servers is generally still done manually by administrators. To overcome this, we need a system that functions to inform threats that occur optimally and be resolved quickly. The IDS network security system was developed using Suricata. Suricata itself will be built using OPNsense. With the Suricata system using OPNsense, it can detect or prevent incoming attacks.